Natural multi-target inhibitors of cholinesterases and monoamine oxidase enzymes with antioxidant potential from skin extracts of Hypsiboas cordobae and Pseudis minuta (Anura: Hylidae) - Spinelli, Roque (2018)
Alzheimer´s disease (AD) is the most common cause of dementia, characterized by loss of selective neuronal and normal brain functions. Every year, ten million new cases are diagnosed worldwide. AD is a complex disease associated with all kind of different pathways, making their simultaneous modulation necessary. Nowadays anti-AD treatments are focused on enzymatic inhibitors. The study of the amphibians? skin had acquired great importance in the fields of biology and human health and represents an attractive and novel source for natural compounds with high potential in the development of new drugs. The present work exhibits the power of amphibian skins as a source of bioactive compounds. Herein we report the activity of extracts of two species from Hylidae family (H. cordobae and P. minuta) as reversible inhibitors of acetylcholinesterase and butyrylcholinesterase enzymes. Furthermore, the extracts inhibit MAO−B enzyme and showed antioxidant activities, acting on four important pathways of AD.